1990
DOI: 10.1177/107110079001100204
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Variations of the Peroneus Quartus Muscle: An Anatomic Study

Abstract: There has been little research concerning this muscle since the 1920s, when Hecker described this muscle to be present in (13%) of his dissections of cadaver legs. The purpose of our dissections was to establish the incidence of the peroneus quartus muscle, its origins, and insertions. One hundred and twenty-four legs from 65 fresh human cadavers were dissected under loupe magnification. When the peroneus quartus tendon was found, its origin, insertion, and anatomic relationship to the peroneus longus and pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
118
2
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(125 citation statements)
references
References 9 publications
1
118
2
4
Order By: Relevance
“…The fourth fibularis muscle as member of a group of accessory fibular muscles has been described as to be unique to humans (Henle, 1871). This supernumerary muscle originates as a slip high up on the fibula between the longus and brevis fibular muscles or from distal part of leg and the distal attachments of the muscle are not fixed (Macalister, 1875;Hecker;Sobel, 1990).The origin of the fibularis quartus from the posterior aspect of the fibula between the brevis and flexor hallucis longus muscles was described (Wachter & Beekman). The fibularis quartus muscle represents an evolutionary step in the development of bipedal posture (Hecker).…”
Section: Discussionmentioning
confidence: 99%
“…The fourth fibularis muscle as member of a group of accessory fibular muscles has been described as to be unique to humans (Henle, 1871). This supernumerary muscle originates as a slip high up on the fibula between the longus and brevis fibular muscles or from distal part of leg and the distal attachments of the muscle are not fixed (Macalister, 1875;Hecker;Sobel, 1990).The origin of the fibularis quartus from the posterior aspect of the fibula between the brevis and flexor hallucis longus muscles was described (Wachter & Beekman). The fibularis quartus muscle represents an evolutionary step in the development of bipedal posture (Hecker).…”
Section: Discussionmentioning
confidence: 99%
“…They showed that it was present in 21.7% of cadavers. The most frequent origin was from the muscle fibres of PB and its most frequent insertion was into the retrotrochlear eminence of the calcaneum.The PQ muscle although usually stems from the peroneus brevis; however some cases of emergence from the PL were also reported i.e., 15% of cases for Sobelet al 5 . In the present case, PQ was found to arise both from the PB and PL.…”
Section: Discussionmentioning
confidence: 99%
“…In different cases of patients with chronic pain and swelling around the ankle after lateral ankle sprain, the surgical exploration revealed the presence of PQ muscle and after conservative treatments failed, surgical resection was found to be more effective treatment 14 . In spite of its shortcomings, the PQ muscle has been used successfully in the reconstruction of the peroneal retinaculum for the treatment of recurrent anterior subluxations of the peroneal tendons and has thus proved to be beneficial 5,15 .…”
Section: Discussionmentioning
confidence: 99%
“…The peroneus quartus muscle was first described by Otto in 1816 [3] and has since been termed the peroneus sextus, peroneus calcaneus externus, peroneocuboidian, peroneus accessorius, peroneus medius [7], and peroneus muscle of the tarsus [1]. Anatomists, surgeons, and radiologists have discovered slight variations in the distal insertion of the peroneus quartus, resulting in both increased and ambiguous nomenclature [8][9][10][11]. The reported points of insertion include (from proximally to distally): retrotrochlear eminence of the calcaneus, the fibular (peroneal) trochlea of the calcaneus, tendons of the fibularis longus and brevis muscles, the cuboid, and the fifth metatarsal [10,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Anatomists, surgeons, and radiologists have discovered slight variations in the distal insertion of the peroneus quartus, resulting in both increased and ambiguous nomenclature [8][9][10][11]. The reported points of insertion include (from proximally to distally): retrotrochlear eminence of the calcaneus, the fibular (peroneal) trochlea of the calcaneus, tendons of the fibularis longus and brevis muscles, the cuboid, and the fifth metatarsal [10,[12][13][14]. In 1923, Hecker [1] classified the peroneus quartus variants into 3 categories according to the insertion onto the calcaneus (peroneocalcaneus externum), cuboid (peroneocuboideus), or tendon of peroneus longus (peroneoperoneolongus).…”
Section: Introductionmentioning
confidence: 99%